The Output Gap and Potential Output in Namibia - Emmanuel Ziramba; Bernie Zaaruka; Johanna Mumangeni; Charlotte Tjeriko; Jaungura Kaune (Journal of Economics and Behavioral Studies, 2019)
The study analysed the behaviour of potential output and output gap for the Namibian economyusing annual data from 1980 to 2016. The study employed the Hodrick-Prescott (HP) filter method and theproduction function approaches to estimate potential output before calculating the output gap. The resultssuggest an annual average growth rate of 3.6 percent in potential output. However, it has been noted that theaverage annual growth rate in potential output has been shifting during the period under review. In fact, theresults suggest an annual average growth rate of 1.6 percent between 1980 and 1985 and an increase to 2.5percent per year for the period 1986 to 1990. Potential output estimates obtained using the productionfunction approach was smooth and stable throughout the study period. The potential output estimatesobtained through the two methods follow the same cyclical movements. The output gap estimates from thetwo techniques are not different from each other, and they appear to move together.